09 Cardiac contraction energetics; a system's view. Issue 24 (24th November 2011) - Deschodt-Arsac, V; Diolez, P
Abstract : To overcome the complexity of intra-organ regulations, we developed MoCA (Modular Control Analysis), a system's level analysis defining heart energetics as a Supply-Demand system. MoCA combines metabolic control analysis with non-invasive 31P NMR measurement of energetic intermediates in intact heart. We used MoCA to demonstrate experimentally for the first time in intact beating isolated rat heart that physiological activation of contraction involves the almost perfect parallel activation of both mitochondria and myofibrils by intracellular Ca 2+ .1 This explains the perfect homeostasis of the energetic intermediate phosphocreatine (PCr) in heart, but not in muscle. Only activation of myofibrils activity (Demand)—either by increasing intracellular Ca 2+ or myofibrils sensitivity to Ca 2+ —triggers activation of contraction.2 By contrast, the Ca 2+ activation of mitochondrial activity (Supply) has strictly no effect on contraction. The inotropic effect is therefore the direct consequence of myofilaments activation and not of the direct effect of calcium on mitochondria. Direct mitochondrial activation by Ca 2+ is however crucial for energetic intermediates homeostasis and normal physiological response (energy balance). In conclusion, any pathological impairment of energy supply will affect integrated heart energetics response and may be analysed by MoCA. Therefore, we now propose to use MoCA to diagnose heart dysfunctions in humans. We are currently developing the clinical application of MoCA by using non-invasive 31P-NMR spectroscopy and time-resolved 3D MRI techniques to access energetics and contractile activity respectively.